PENGARUH CSR TERHADAP KEMAMPUAN INOVASI DAN KINERJA UMKM (STUDI KASUS PENYALURAN DANA CSR PT SPHC PADA UMKM BUNGA KOPENG) - Evinta Amalia Nurhidayah; Infijarun Ni’am (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2022)
This study aims to provide empirical evidence regarding the effect of Corporate Social Responsibility (CSR) on the Innovation Ability and Performance of MSMEs in Kopeng and also to find out if innovation ability mediates the relationship between CSR and MSME performance. The method used in this study is a quantitative method with data collection techniques using the Purposive Sampling method. The sample taken and used as a research sample is a member of the Memayu Jogo Tonggo cooperative who works as a flower seller. The data analysis technique used multiple regression analysis. The results of CSR research have a positive effect on MSME Performance, CSR has a positive effect on Innovation Ability, Innovation Ability has no influence on MSME Performance. Innovation ability does not mediate the relationship between CSR and MSME performance.